2012
DOI: 10.1186/1471-2261-12-32
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic premature ventricular contractions and ventricular tachycardias originating from the vicinity of tricuspid annulus: Results of radiofrequency catheter ablation in thirty-five patients

Abstract: BackgroundIn recent years, catheter ablation has increasingly been used for ablation of idiopathic premature ventricular complexes (PVCs) or ventricular tachycardias (IVTs). However, the mapping and catheter ablation of the arrhythmias originating from the vicinity of tricuspid annulus (TA) may not be fully understood. This study aimed to investigate electrophysiologic characteristics and effects of radiofrequency catheter ablation (RFCA) for patients with symptomatic PVCs and IVTs originating from the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 13 publications
3
37
1
Order By: Relevance
“…A small number of cases of idiopathic VAs have been reported to originate from the tricuspid annulus [8]. Mapping and catheter ablation of the arrhythmias originating from the tricuspid annulus has been fully understood, and radiofrequency catheter ablation is an effective curative therapy for symptomatic PVCs originating from the vicinity of tricuspid annulus [9]. The standard catheter ablation procedure is performed via the femoral vein.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of cases of idiopathic VAs have been reported to originate from the tricuspid annulus [8]. Mapping and catheter ablation of the arrhythmias originating from the tricuspid annulus has been fully understood, and radiofrequency catheter ablation is an effective curative therapy for symptomatic PVCs originating from the vicinity of tricuspid annulus [9]. The standard catheter ablation procedure is performed via the femoral vein.…”
Section: Introductionmentioning
confidence: 99%
“…We and other investigators have recently demonstrated that QRS duration, R-wave transition in the precordial leads, QS pattern in lead V1, and polarity of the QRS complex in the inferior leads were useful to distinguish between PVCs/IVTs originating from the septal portion and free wall of tricuspid annulus [8], [9]. A monophasic tall R pattern in lead I, low R wave in leads II and aVF, particularly lower R wave in lead III than in lead II, R wave in lead aVL, relatively narrow QRS duration, QS pattern in lead V1, and tall R wave in V5 and V6 suggest the PVCs/IVTs origin from the RV septum near the His-bundle [10].…”
Section: Discussionmentioning
confidence: 98%
“…With the development of electrophysiology and radiofrequency ablation, several studies [9][10][11][12][13] have described the criteria to distinguish PVC origin according to the features of the 12-lead electrocardiogram. Site-specific crite- ria of PVCs also have been reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This type of PVC is generally considered to be of tricuspid annulus origin. 11,16) 3) PVCs LBBB (RBBB)-I: a RBBB morphology with upward main QRS wave pattern in lead V1 and a large R pattern of QRS in leads II and III, and aVF is considered to be of LVOT origin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation